Exploring Handgrip Strength as a Cross-cultural Correlate of Body Composition and Upper Body Strength in Older Adults from Costa Rica and Kansas - Moncada Jiménez, José (2023)
Sarcopenia and disability in older adults are often characterized by body composition measurements; however, the gold standard of body composition measurement, dual-energy X-ray absorptiometry (DEXA), is expensive to acquire and maintain, making its use in low and middle income countries (LMIC) it out-of-reach in developing nations. Because these LMIC will bear a disproportionate amount of chronic disease burden due to global aging trends, it is important that reliable, low-cost surrogates need to be developed. Handgrip strength (HGS) is a reliable measure of disability in older adults but has not been used widely in diverse populations. This study compared HGS to multiple measurements of body composition in older adults from the US (Kansas) and a middle-income country (Costa Rica) to test if HGS is a cross-culturally appropriate predictive measure that yields reliable estimates across developed and developing nations. Percent body fat (%BF), lean tissue mass index (LTMI), appendicular lean soft tissue index (ALSTI), body fat mass index (BFMI), bone mineral density (BMD), and HGS were measured in older Costa Ricans (n=78) and Kansans (n=100). HGS predicted lean arm mass with equal accuracy for both samples (p≤0.05 for all groups), indicating that it is a reliable, low-cost and widely available estimate of upper body lean muscle mass. Older adults from Costa Rica showed diferent body composition overall and HGS than controls from Kansas. Handgrip operates equivalently in the US and Mesoamerica and is a valid estimate of lean arm muscle mass as derived by the more expensive DEXA.